A novel composite inflammatory–metabolic index for long-term prognosis after TAVR: the modifying role of left ventricular ejection fraction - Haitham Abu Khadija; Nizar Abu Hamdeh; Duha Najajra; Kareem Ibraheem; Jebrin Alkrinawi; Osama Hroub; Yahya Z. Fraitekh; Mohammad Masu'd; Abdalaziz Darwish; Mohammad Alnees (Frontiers in Cardiovascular Medicine, 2026)
Background Metabolic dysfunction and systemic inflammation are increasingly recognized as important determinants of outcomes after transcatheter aortic valve replacement (TAVR). However, whether their prognostic impact differs according to baseline left ventricular systolic function remains unclear. Objectives To evaluate the association between the TyG–SII composite index (TSI), an inflammatory–metabolic biomarker, and long-term outcomes after TAVR and to determine whether baseline left ventricular ejection fraction (LVEF) modifies this association. Methods We conducted a retrospective cohort study of patients who underwent TAVR between December 2015 and March 2025. Patients were stratified according to baseline LVEF (≤40% vs. >40%). To reduce confounding, a 1:4 exact matched cohort was constructed according to sex, age category, calendar period of TAVR, and valve type ( n = 646). TSI was calculated from pre-procedural laboratory values and analyzed as a continuous standardized variable (per 1-SD increase). Long-term all-cause mortality was assessed using Cox proportional hazards models stratified by LVEF. A separate 1:4 time-dependent matched cohort ( n = 224) was used to evaluate the association between LVEF and long-term hemodynamic valve deterioration (HVD). Results During follow-up, 187 deaths occurred: 51 among patients with LVEF ≤ 40% (33.3%) and 136 among those with LVEF > 40% (27.6%). Kaplan–Meier analysis showed no significant difference in overall survival between LVEF groups (log-rank p = 0.225). In multivariable analyses, each 1-SD increase in standardized TSI was independently associated with higher mortality among patients with LVEF ≤ 40% (adjusted HR, 1.38; 95% CI, 1.10–1.73; P = 0.005), but not among those with LVEF > 40% (adjusted HR, 1.02; 95% CI, 0.84–1.24; P = 0.818). Patients with reduced LVEF also exhibited a higher long-term risk of HVD compared with matched controls (adjusted HR, 1.71, 95% CI, 1.00–2.91, p = 0.048). Conclusions In patients undergoing TAVR, greater inflammatory–metabolic burden, as reflected by TSI, was independently associated with long-term mortality among those with reduced LVEF. Reduced LVEF was also associated with a higher long-term risk of HVD; however, this exploratory finding requires confirmation in larger prospective studies.